2021
DOI: 10.1002/rcs.2359
|View full text |Cite
|
Sign up to set email alerts
|

Proof of concept study for using UR10 robot to help total hip replacement

Abstract: Background:The demand for total hip replacement (THR) for treating osteoarthritis has grown substantially worldwide. The existing robotic systems used in THR are invasive and costly. This study aims to develop a less-invasive and low-cost robotic system to assist THR surgery.Methods: A preliminary robotic reaming system was developed based on a UR10 robot equipped with a reamer to cut acetabulum. A novel approach was proposed to cut through a 5 mm hole in femur such that the operation is less invasive to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The test results are Exp 8 and Exp 11 for the bone block #15 and #30, respectively. To compare different categories of cutting methods, the experiments were repeated for both robotic reaming 18 and conventional (manual) reaming. The cutting diameters also ranged from 48 mm through 54 mm in 2 mm increments and were performed 3 times per cutting diameter.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The test results are Exp 8 and Exp 11 for the bone block #15 and #30, respectively. To compare different categories of cutting methods, the experiments were repeated for both robotic reaming 18 and conventional (manual) reaming. The cutting diameters also ranged from 48 mm through 54 mm in 2 mm increments and were performed 3 times per cutting diameter.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…The high financial cost of the system, however, makes its widespread use prohibitive. Alternatively, a low‐cost robotic system based on the UR10 collaborative robotic arm (Universal Robots) equipped with a reamer has been studied with bone block models, demonstrating a higher accuracy of robotic‐assisted reaming as compared to reaming by hand 18 . Reamers (Figure 2) may be prone to generate excessive heat leading to osteonecrosis due to the large cutting contact area, and may lead to aseptic loosening 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it was shown that a simple change in configuration could improve the surface finish in a polishing task by absorbing vibrations [ 17 ]. More recently, an admittance control framework was used for machining bone for use in hip replacement surgery [ 36 ]. Adopting an appropriate arm posture could further enhance the admittance control.…”
Section: Case Studiesmentioning
confidence: 99%
“…There are many scenarios where exploiting the passive stiffness in a robotic arm can be used to improve task performance. For example, it was shown that a simple change in More recently, an admittance control framework was used for machining bone for use in hip replacement surgery [36]. Adopting an appropriate arm posture could further enhance the admittance control.…”
Section: Planning In Robotic Tasksmentioning
confidence: 99%